Compensation Suitability On Accounting Fraud Tendency With Leadership Style And Internal Control Systems As Moderation - Gede Rudi Harta Pratama Giri; Made Gede Wirakusuma (E-Jurnal Akuntansi, 2025)
Accounting fraud tendencies are often carried out to gain benefits for an organization or individual. The financial performance report of PERUMDA Air Minum, the location of this study, shows a decline from 2018-2020. The purpose of this study is to obtain empirical evidence regarding the effect of compensation suitability on accounting fraud tendencies and to determine the moderating effect of internal control systems and leadership styles on compensation suitability tendencies. The research sample consisted of 81 employees from PDAM Sewakadarma, PDAM Mangutama, and PDAM Hita. Data collection was carried out using a Likert Scale questionnaire 4. Data analysis used, namely MRA using SPSS. The results of this study found that compensation suitability has a significant negative effect on accounting fraud tendencies, meaning that increasing compensation suitability will reduce accounting fraud tendencies. Internal control systems and leadership styles strengthen the effect of compensation suitability in reducing accounting fraud tendencies, meaning that the stronger the internal control system and leadership style, the stronger the compensation suitability in reducing accounting fraud tendencies.